DAVID AND BETHSHEBA: ADULTERY OR RAPE? - Pardede, Harold; Iman, Anugrah Saro (Moriah Theological Seminary, 2025)
Different scholars offer various perspectives on the David and Bathsheba plotline part of 2 Samuel 11. Certain interpretations view it as a romantic tale, while others consider it a narrative of infidelity, meanwhile, some scholars interpret it as an account of David’s crime of sexually assaulting another man’s wife. Through this study, the author aims to clarify whether Bathsheba engaged in adultery with David or was a victim of rape. The research employs a qualitative approach with a descriptive analysis method. The author examines 2 Samuel 11 by conducting exegesis and analyzing the historical context provided within the text. Arguing from the study's results, the author posits Bathsheba as a victim of David's authority, not rape. This narrative urges caution in how we interpret it, as failing to view Bathsheba’s story as one of adultery may lead us to overlook the prevalence of sexual sin among God’s people and foster a tendency to unfairly blame women as the cause of adultery or rape. Berbagai sarjana menawarkan perspektif yang berbeda-beda mengenai alur cerita Daud dan Batsyeba dalam 2 Samuel 11. Beberapa tafsir memandangnya sebagai kisah romantis, sementara yang lain menganggapnya sebagai narasi tentang perselingkuhan. Di sisi lain, beberapa sarjana menafsirkannya sebagai catatan tentang kejahatan Daud yang melakukan pelecehan seksual terhadap istri orang lain. Melalui studi ini, penulis bertujuan untuk mengklarifikasi apakah Batsyeba terlibat dalam perselingkuhan dengan Dauda atau menjadi korban pemerkosaan. Penelitian ini menggunakan pendekatan kualitatif dengan metode analisis deskriptif. Penulis mengkaji 2 Samuel 11 melalui eksegesis dan menganalisis konteks historis yang terdapat dalam teks. Berdasarkan hasil penelitian, penulis berpendapat bahwa Batsyeba adalah korban dari kekuasaan Daud, bukan pemerkosaan. Narasi ini mendorong kehati-hatian dalam menafsirkannya, karena gagal melihat kisah Batsyeba sebagai kasus perzinahan dapat membuat kita mengabaikan prevalensi dosa seksual di kalangan umat Allah dan memicu kecenderungan untuk menyalahkan perempuan secara tidak adil sebagai penyebab perzinahan atau pemerkosaan.